Effectiveness of an online education intervention on stress and coping of family members after placing a relative with dementia into a residential care facility: protocol of a randomised controlled trial - Zhaozhao Hui; Chen Yang; Jieqiong Li; Diana Tze Fan Lee (BMC Geriatrics, 2020)
Abstract Background After residential care placement, family members may be exposed to stressors like difficulty in role changes, interpersonal conflict with facility staff, and emotional torment. These can threaten family members’ own health and well-being and even influence the extent they involve in their relative’s care. This study aims to evaluate an online education intervention for Chinese family members whose relatives with dementia have been placed into a residential care facility. Methods This protocol describes a two-arm randomised controlled trial. A total of 150 family members of residents with dementia will be recruited from four to six residential care facilities in Xi’an, Shaanxi, China and randomly allocated to either the intervention or control group. Family members in the intervention group will receive a six-week group-based online education intervention, while those in the control group will receive routine care. Family members’ stress, coping, caregiving burden, and family involvement, as well as their relative’s behavioural and psychological symptoms of dementia will be assessed at immediately post-intervention and six-week follow-up. Effectiveness of the intervention will be analysed by generalised estimating equation model, based on the intention-to-treat principle. A process evaluation of the intervention will also be undertaken. Discussion This study will be of great significance in addressing family members’ stressors after institutionalising a relative with dementia and promoting the implementation of family-centred care in practice especially in residential care facilities. Trial registration Chinese Clinical Trial Registry, ChiCTR1900024582 , Registered 18 July 2019.